(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Text in process of completion, not subject to referee review, of Report at the Conference on "La libertà religiosa nell’età post-secolare" in Lugano, Faculty of Theology (27-28 March 2014). SOMMARIO: 1. Introduction: the social power of religions and the need for dialogue - 2. Law as a required hurdle to the “disclaimers” of religious freedom - 3. The restrictions to the exercise of religious freedom: an overview - 4. Religious freedom and social welfare: an inseparable duo - 5. Brief conclusions.